Photocatalytic Oxidative C–H Thiolation: Synthesis of Benzothiazoles and Sulfenylated Indoles - Dinh, Andrew N.; Nguyen, Ashley D.; Aceves, Ernesto Millan; Albright, Samuel T.; Cedano, Mario R.; Smith, Diane K.; Gustafson, Jeffrey L. (Synlett, 2019)
We report studies on the photocatalytic formation of C–S bonds to form benzothiazoles via an intramolecular cyclization and sulfenylated indoles via an intermolecular reaction. Cyclic voltammetry (CV) and density functional theory studies suggest that benzothiazole formation proceeds via a mechanism that involves an electrophilic sulfur radical, while the indole sulfenylation likely proceeds via a nucleophilic sulfur radical adding into a radical cationic indole. These conditions were successfully extended to several thiobenzamides and indole substrates.
Keywords: photoredox catalysis; benzothiazole; indole; thiolation; C–H functionalization